Design and Implementation of DHT Algorithm for NDN - Kai Lei; Meng Yuan (Dianxin kexue)
A novel distributed Hash table（DHT）algorithm under named data networking（NDN）, which was called ndnDHT, was proposed. The algorithm brings the DHT to NDN for the first time. A new binary method using the structure of NDN was designed. By mapping the key space to the space of NDN, the binary method solves the operations such as routing and retransmission. Besides, a dynamic selection method of node identifier distribution was proposed to balance the load of ndnDHT algorithm. Finally, ndnDHT algorithm based on NS-3 and ndnSIM was implemented. The experimental result shows that the ndnDHT algorithm is effective.